GAMELAN POLENG â€œSINERGISITAS HARMONI WARNAâ€ - I Wayan Diana Putra (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2013)
This article is an analysis of the process of creating a new musical composition entitled Gamelan Poleng. This musicalcomposition was inspired by the observation of a visual structure, poleng (a checked pattern), which is well known on theIsland of Bali (and also in Central Java). This checked pattern, in sacred imagery, is an element that is inseparable from thehearts and minds of the Balinese people in particular. In addition to its sacred or auspicious meaning, poleng also has apsychological connection with values of togetherness in social activities within a community. It is this humanistic psychologicalmeaning of poleng that was used as the idea for creating a new composition of gamelan music. The idea of poleng inits psychological perspective was sublimated into the idea for the content and extra-musical treatment of a gamelan composition.This new conception of poleng in a psychological context was then developed through the medium of gamelan musicand it is hoped that the result will provide a reflection of the importance of values of uniformity and togetherness.Keywords: Poleng, Psychology, Gamelan Music Composition